MENGGALI NILAI PINTU GEBYOK ARSITEKTUR RUMAH ADAT JAWA: EKSPLORASI ETIKA JAWA FRANZ MAGNIS SUSENO - Dhewangga Priatmojo; Tejo Bagus Sunaryo (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2025)
This research aims to examine the elements of Javanese ethics found in the Gebyok doors of traditional Javanese houses. Javanese ethics is a systematic study or review of a view, rules, and related to moral terms in Javanese society. The Gebyok door in the traditional Javanese house is one of the Javanese cultural products that contains elements of Javanese ethics. The concept of Javanese ethics can be found in the Gebyok door. Gebyok doors in traditional Javanese houses have a different size from the doors found in Javanese houses in general in the current area. Gebyok function as a partition that usually has a door as a wall element in a Javanese house. The method used is qualitative research with a descriptive analysis approach. The results of this study illustrate a number of values is realized in the form of Gebyok doors of Javanese traditional house architecture buildings that use the Kupu Tarung model. The shape of the Gebyok door, which is made shorter, symbolically teaches others to be andhap asor (polite) and know themselves, while the door made used the Kupu Tarung model symbolically teaches the owner of the house to always be friendly, open, open-minded, by accepting anyone who comes as his guest. Thus, harmony is achieved, the psychological state is inner peace, tranquility and a sense of security (slamet) in the life of Javanese society.